Predicting safe tonsillectomy for ambulatory surgery - Raja Lope Ahmad, Raja Ahmad Al'konee; Abdullah, Kahairi; Asha'ari, Zamzil Amin; Ab Rahman, Jamalludin (Elsevier, 2010)
Objectives: To assess the safety of tonsillectomy procedure in local setting.